Ca2+ Regulates the Kinetics of Synaptic Vesicle Fusion at the Afferent Inner Hair Cell Synapse - Huang, Chao-Hua; Moser, Tobias (Frontiers in Cellular Neuroscience, 2018)
The early auditory pathway processes information at high rates and with utmost temporal fidelity. Consequently, the synapses in the auditory pathway are highly specialized to meet the extraordinary requirements on signal transmission. The calyceal synapses in the auditory brainstem feature more than a hundred active zones with thousands of releasable synaptic vesicles (SVs). In contrast, the first auditory synapse, the afferent synapse of inner hair cells (IHCs) and type I spiral ganglion neurons (SGNs), typically exhibits a single ribbon-type active zone tethering only tens of SVs resulting in a highly stochastic pattern of transmitter release. Spontaneous excitatory postsynaptic currents (sEPSCs), besides more conventional EPSCs with a single peak, fast rise and decay (compact), also include EPSCs with multiple peaks, variable rise and decay times (non-compact). The strong heterogeneity in size and shape of spontaneous EPSCs has led to the hypothesis of multivesicular release (MVR) that is more (compact) or less (non-compact) synchronized by coordination of release sites. Alternatively, univesicular release (UVR), potentially involving glutamate release through a flickering fusion pore for non-compact EPSCs, has been suggested to underlie IHC exocytosis. Here, we further investigated the mode of release by recording sEPSCs from SGNs of hearing rats while manipulating presynaptic IHC Ca2+ influx by changes in extracellular [Ca2+] ([Ca2+]e) and by application of the Ca2+ channel antagonist, isradipine, or the Ca2+ channel agonist, BayK8644 (BayK). Our data reveal that Ca2+ influx manipulation leaves the distributions of sEPSC amplitude and charge largely unchanged. Regardless the type of manipulation, the rate of sEPSC decreased with the reduction in Ca2+ influx. The fraction of compact sEPSCs was increased in the presence of BayK, an effect that was abolished when combined with decreased [Ca2+]e. In conclusion, we propose that UVR is the prevailing mode of exocytosis at cochlear IHCs of hearing rats, whereby the rate of exocytosis and the kinetics of SV fusion are regulated by Ca2+ influx.